(untitled) (Diversity Research: Journal of Analysis and Trends, 2023)
The article highlights the problem of developing the culture of speech of schoolchildren in Russian language and literature lessons, instilling in them respect for words, developing creative potential and communicative competence. The task of a teacher of Russian language and literature is to cultivate speech culture, to reveal to students the expressive power of our language, its euphony and rhythm.